Occupational Anxiety Burnout during The COVID-19 Pandemic, A Review - Yosef Parulian Situmorang (The Indonesian Journal of Community and Occupational Medicine, 2024)
Introduction: Violations of providing excessive working hours to health workers occurred during the COVID-19 pandemic. Doctors and nurses often have to work longer hours than they should during the pandemic with little compensation. The large number of patients during the pandemic overwhelmed health workers and many of them fell ill or died. However, this is not counted as an occupational disease.Methods: A literature review was conducted to explore instances of scientific misconduct in occupational health studies related to Occupational Anxiety Burnout in health worker during pandemic covid-19. The sources were taken from Google Scholar and Scopus. From the entire search, 5 relevant studies were reviewed.Results: Occupational anxiety burnout could result from concerns about the risk of infection and lack of confidence in the safety measures adopted. Conclusions: Although there are no reports of complaints of burnout as an occupational disease among health workers in Indonesia during COVID-19 pandemic, it is more important to reorganize the work, so as to reduce the effort made by each individual worker.